2006
DOI: 10.1097/01.shk.0000209522.28120.c8
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Prevents Hemorrhage-Associated Lethality and Affects the Acetylation Pattern of Cardiac Histones

Abstract: Pharmacological inhibitors of histone deacetylases (HDAC) demonstrate cytoprotective effects both in vitro and in vivo. In this study, we investigated whether valproic acid (VPA), a known mood stabilizer and anticonvulsant with HDAC-inhibiting activity, improves survival following otherwise lethal hemorrhage in rats. We found that preinsult injection of VPA (300 mg/kg, twice) prolonged the survival of severely hypotensive animals up to 5 times. VPA treatment increased the acetylation of nonhistone and histone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…We have shown previously that severe hemorrhage is associated with HDAC/HAT imbalance, which influences the acetylation status of cardiac, lung, and liver histones, and that it can be corrected by treatment with pharmacologic HDAC inhibitors (HDACI) [1][2][3][4][5]9]. In a rodent model of lethal hemorrhagic shock, we have recently reported that post-shock administration of HDACI, such as VPA or suberoylanilide hydroxamic acid, significantly improves survival even in the absence of conventional fluid resuscitation [4].…”
Section: Discussionmentioning
confidence: 98%
“…We have shown previously that severe hemorrhage is associated with HDAC/HAT imbalance, which influences the acetylation status of cardiac, lung, and liver histones, and that it can be corrected by treatment with pharmacologic HDAC inhibitors (HDACI) [1][2][3][4][5]9]. In a rodent model of lethal hemorrhagic shock, we have recently reported that post-shock administration of HDACI, such as VPA or suberoylanilide hydroxamic acid, significantly improves survival even in the absence of conventional fluid resuscitation [4].…”
Section: Discussionmentioning
confidence: 98%
“…We thus decided to have 12 animals per group, anticipating the survival in the no-treatment group to be ϳ10% based on our previous study using similar model, 28 and unpublished pilot studies. We also reasoned that if treatment with valproic acid (VPA) and suberoyanilide hydroxamic acid (SAHA) yielded similar survival rates, then they could be combined together to increase the sample size and compare the HDACI treated (VPA ϩ SAHA) animals against the controls.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…This is similar to what we have shown previously with pre-hemorrhage administration of VPA. 28 However, as time to death was not a predefined endpoint in the current study, it was not subjected to statistical analysis. All the Sham and saline resuscitated animals survived for 3 hours and eventually to one week.…”
Section: Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Valproic acid, a histone deacetylase inhibitor, has been shown in several different animal models to improve survival in hemorrhagic shock. [15][16][17] noted that postshock administration of valproic acid (without fluid resuscitation) improved early survival in a rat model of hemorrhagic shock. This same group evaluated the effect of valproic acid in a large animal model of trauma and hemorrhagic shock.…”
mentioning
confidence: 98%